2017
DOI: 10.30924/mjcmi/2017.22.2.35
|View full text |Cite
|
Sign up to set email alerts
|

Shift work, emotional labour and psychological well-being of nursing staff

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 35 publications
0
17
0
1
Order By: Relevance
“…If professional nurses view emotional labor as an opportunity to express their positive emotions and feel a sense of accomplishment, rather than merely as a factor that obstructs their nursing service, positive psychological reactions might be induced, even if they must act according to their organization's specified norms concerning emotional expression (Hong & Kwon, ). According to the majority of existing research, emotional labor negatively affects nurses' job attitudes and psychological well‐being (Cheng et al, ; Hulsheger & Schewe, ; Vermaak et al, ). However, considering previous research findings indicating that emotional labor has no adverse influence on the quality of nursing care (Lee & Kim, ) and its positive effects on quality of care, performance, and patient satisfaction (Badolamenti et al, ), we recommend conceptualizing emotional labor as a neutral influence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If professional nurses view emotional labor as an opportunity to express their positive emotions and feel a sense of accomplishment, rather than merely as a factor that obstructs their nursing service, positive psychological reactions might be induced, even if they must act according to their organization's specified norms concerning emotional expression (Hong & Kwon, ). According to the majority of existing research, emotional labor negatively affects nurses' job attitudes and psychological well‐being (Cheng et al, ; Hulsheger & Schewe, ; Vermaak et al, ). However, considering previous research findings indicating that emotional labor has no adverse influence on the quality of nursing care (Lee & Kim, ) and its positive effects on quality of care, performance, and patient satisfaction (Badolamenti et al, ), we recommend conceptualizing emotional labor as a neutral influence.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these previous studies have reported that emotional labor negatively affects nurses' job attitudes (e.g. turnover intention, job satisfaction, organizational commitment, and burnout) and psychological well‐being (Cheng, Bartram, Karimi, & Leggat, ; Hulsheger & Schewe, ; Vermaak, Görgens‐Ekermans, & Nieuwenhuize, ), while organizational communication satisfaction positively affects this variable (Je & Han, ; Kim & Lee, ). However, little is known about how emotional labor positively affects job‐related performance in the nursing profession.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed earlier, employee's well-being is one of the key concerns by the organization. Study shows emotional labour bring significant impacts towards psychological well-being among nursing staffs (Vermaak et al, 2017). In addition, nurses who experienced higher level of emotional labour will result in emotional exhaustion which is the burnout factors that is categorized under well-being (Kinman & Leggetter, 2016).…”
Section: Emotional Labour and Employee's Well-beingmentioning
confidence: 97%
“…On the other word, psychological well-being can be defined as personal's experience towards the achievement and recognition, mental health, satisfaction, purpose of life and social relationship. According to the study of Vermaak, Görgens-ekermans, & Nieuwenhuize (2017), psychological well-being at work is significant for employee's retention and satisfaction. Besides, psychological well-being also result in outcome such as employee's performance (Peiro, Tordera, & Lorente, 2014).…”
Section: Concept and Study Of Psychological Well-beingmentioning
confidence: 99%
“…Hochschild (1983) själv poängterar att teorin om känsloarbete är överförbar på alla yrken där den arbetande samtidigt hanterar sina egna och andras känslor. Trots den kritik som framförts har hennes förståelseram applicerats på en mängd olika professioner och forskningsområden inom exempelvis sjukvården (Vermaak, Görgens-Ekermans & Nieuwenhuize, 2017;Delgado et al, 2017), olika former av kundtjänstarbete (Deery, Iverson & Walsh, 2002;Cosette & Hess, 2015) och för att studera lärare (Yilmaz et al, 2015;Springer & Oleksa, 2017). Inom socialt arbete har exempelvis Kanasz och Zielińska (2017) beskrivit känsloarbete som en central del av socialarbetarens brukararbete.…”
Section: Appliceringar Av Hochschilds Teoriunclassified